From Neoliberalism to Economic Nationalism: Implications of Deglobalisation for African Security and Development - OMOTAYO, Kolawole C.; ABDULYAKEEN, Abdulrasheed (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
The erosion of neoliberal orthodoxy alongside accelerating deglobalization and the resurgence of economic nationalism signals a profound reconfiguration of the global economic order. While these dynamics are well documented in advanced economies, their implications for Africa remain insufficiently explored. This study examines how shifts in the global political economy shape African state capacity, developmental trajectories and vulnerability to emerging economic and security risks. Drawing on dependency theory and critical political economy, the analysis employs a qualitative comparative methodology, combining case studies of Nigeria, South Africa and Kenya with discourse analysis of policy documents and scholarly literature. The findings reveal that the retreat of neoliberal globalization presents both constraints and opportunities: economic nationalism opens space for industrial policy, regional value chain development and technological upgrading, yet protectionism in the Global North intensifies Africa’s marginalization in global trade and investment. These opportunities are further constrained by weak regional coordination and limited institutional capacity, heightening exposure to external shocks, inequality and insecurity. The study argues that navigating the post-neoliberal global order requires a strategic recalibration of Africa’s development agenda through deeper regional integration, investment in domestic technological capabilities and enhanced collective bargaining in multilateral economic forums.